Participatory Communication Referred to Meta-Design Approach through the FleXpeaker™ Application of Innovative Material in Exhibition Design - Su, Pei-Hsuan (Advances in Technology Innovation, 2016)
Modelling a communication system in material culture today always involves with objects, people, organizations, activities and interrelationships among them. The researcher suggests bringing together stakeholders engaged to exchange ideas, which the interactions relate to multiple professions and disciplines in a participatory scope of communication system. Owing to the invention of digital media, the status quo of images and sounds has revolutionized and caused changes of the mode of art exhibitions that produce activities and aesthetic concepts in terms of numerical representation, modularity, automation, visual variability and transcoding. Underlying a participatory-design approach, the research emphasizes a co-creative meta-interpretation of museum‟s visitors. In addition, the research delves further into the use of new media-FleXpeaker™ [ITRI], as the carrier. Combining art and design with innovative technology, the research focuses on examining design objects and innovative material which are applied in new media art and exhibition, in the hope to find new angles of participatory interpretation of the “integrated innovation” in curating an exhibition.